Values of Novel 99 Lights in the European Sky by Hanum Salsabiela and Rangga Almahera - Rianawati, Rianawati; Nurasmah, Nurasmah (Universitas Malikussaleh, 2020)
This study is motivated by moral learning which sometimes makes students bored. Text books or modules that contain moral lessons, make students lazy to read them. Students only get knowledge about the morals of learning through textbooks, modules, from information conveyed by the teacher. Students also do not know the meaning, do not appreciate, and do not know how to apply morals in real life everyday. Moral learning in schools is only normative and dogmatic in nature, so teachers only pay attention to the cognitive aspects, while the psychomotor and affective aspects receive less attention. Novels are one source of moral learning. This is because the figures and settings in the novel can be used as examples and guidelines for students in living moral lives in society. The focus of this research is: Moral values in the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela and Rangga Almahendra. To answer the focus of the research, the research questions are; 1). How do the values of human morals towards Allah SWT in the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela and Rangga Almahendra.2). How do the values of human morals towards themselves, 3). How do the moral values of humans towards fellow humans in the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela and Rangga Almahendra. 3). How do the moral values of humans against fellow Muslims. The purpose of this study is to describe and analyze the moral values in the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela and Rangga Almahendra. This research method is qualitative. This is because the object and source of this research is the text of the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela and Rangga Almahendra. Researchers become a key instrument because researchers who read critically the text of the novel. After reading intensively and critically, researchers describe, interpret, and analyze data to answer the focus of the research problem. The data in the form of words, sentences, and paragraphs. In analyzing the data, researchers used the hermeneutic technique. The results of the analysis in this study indicate that the novel 99 Cahaya di Langit Eropa is an Islamic novel that contains moral values. Moral values contained in the novel 99 Cahaya di Langit Eropa are moral values towards Allah SWT are worship prayers, fasting and reading the Qur'an. Moral values to yourself are honesty, patience, and sincerity. Moral values towards fellow human beings are tolerance and helping. While the moral values of fellow Muslims are greeting, fulfilling invitations, and advising each other.